Teacher Professionalism and English Learning Achievement - Fadli, Muhammad (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This study investigates the effect of teacher certification on students’ English learning achievement in a vocational high school context. The research employed a causal-comparative quantitative design involving 80 students divided equally into two groups: those taught by certified English teachers and those taught by non-certified teachers. Data were collected through achievement tests and analyzed using descriptive statistics, normality and homogeneity tests, and an independent samples t-test. The results revealed a significant difference between the two groups (t(78) = 1.988, p = 0.025, one-tailed), indicating that students taught by certified teachers achieved higher mean scores (M = 60.50) than those taught by non-certified teachers (M = 53.70). The effect size (Cohen’s d = 0.45) suggests a moderate but educationally meaningful impact of certification on learning outcomes. The findings confirm that teacher certification contributes positively to students’ English achievement by enhancing teachers’ pedagogical competence, professional conduct, and instructional effectiveness. However, the influence of certification is context-dependent and moderated by factors such as teaching practices, institutional support, and the quality of professional development. It is therefore concluded that teacher certification should not be viewed as an endpoint but as a continuous process of professional learning that sustains teaching quality and fosters students’ academic success.